Contribution of the Heavy Equipment Concentration Industry Class Program to Work Readiness in Line with Industry 4.0 Requirements at Vocational High School - Purwanto, Finto; Nurhadi, Didik; Widiyanti, Widiyanti (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine how the concentration of heavy equipment in industrial classes contributes to the work readiness of Vocational High School graduates, particularly in terms of meeting the demands of Industry 4.0. This research employs a literature review approach by analyzing relevant studies, reports, and publications on vocational education, work readiness, and competencies in the digital era. The findings indicate that the heavy equipment concentration industrial class program enhances graduates' work readiness through the integration of up-to-date technology in the curriculum and a practice-based learning model that develops both technical and soft skills. Graduates are expected to possess technological literacy, problem-solving abilities, and adaptability to digitalization and automation in modern industries. However, this study is limited to secondary data analysis and lacks empirical field data, which should be addressed in future research. The findings have broader implications not only for education but also for the social and economic dimensions of vocational development. By strengthening collaboration between schools and industries, this model enhances graduate employability, promotes local economic growth, and cultivates a skilled workforce aligned with national industrial transformation objectives. Overall, the program has a positive impact; nevertheless, curriculum updates are essential to remain responsive to ongoing industrial changes.